Spectral functions of non-essentially self-adjoint operators - Falomir, Horacio Alberto (2012)
One of the many problems to which Dowker devoted his attention is the effect of a conical singularity in the base manifold on the behavior of the quantum fields. In particular, he studied the small-t asymptotic expansion of the heatkernel trace on a cone and its effects on physical quantities as the Casimir energy. In this paper, we review some peculiar results found in the last decade, regarding the appearance of non-standard powers of t, and even negative integer powers of log t, in this asymptotic expansion for the self-adjoint extensions of some symmetric operators with singular coefficients. Similarly, we show that the ? -function associated with these self-adjoint extensions presents an unusual analytic structure. © 2012 IOP Publishing Ltd.